Spatial Resolution of Attenuation Imaging - KLIMONDA, Ziemowit; LITNIEWSKI, Jerzy; NOWICKI, Andrzej (Archives of Acoustics, 2009)
The attenuating properties of biological tissue are of great importance in ultrasonic examination even though its anatomical variability limits diagnostics effectiveness. We are currently developing a technique for parametric imaging of attenuation and we intend to apply it for in vivo characterization of tissue. The diagnostic usefulness of the proposed technique crucially depends on the precision of the attenuation estimate and the resolution of the parametric image. These two parameters are highly correlated, since the resolution is reduced whenever averaging is used to minimize the errors introduced by the random character of the backscatter. Here we report on the results of numerical processing of both, simulated and recorded from a tissue-mimicking phantom echoes. We have analyzed the parameters of the estimation technique and examined their influence on the precision of the attenuation estimate and on the parametric image resolution. The optimal selection of attenuation image parameters depending on its intended diagnostic use, was also considered.